Ranitidine and finasteride inhibit the synthesis and release of trimethylamine N-oxide and mitigates its cardiovascular and renal damage through modulating gut microbiota - Liu, Junfeng (Int J Biol Sci, 2020)
Trimethylamine N-oxide (TMAO) leads to the development of cardiovascular and chronic kidney diseases, but there are currently no potent drugs that inhibit the production or toxicity of TMAO. In this study, high-fat diet-fed ApoE-/- mice were treated with finasteride, ranitidine, and andrioe. Subsequently, the distribution and quantity of gut microbiota in the faeces of the mice in each group were analysed using 16S rRNA sequencing of the V3+V4 regions. Pathological examination confirmed that both ranitidine and finasteride reduced atherosclerosis and renal damage in mice. HPLC analysis also indicated that ranitidine and finasteride significantly reduced the synthesis of TMAO and the TMAO precursor delta-Valerobetaine in their livers. The 16S rRNA sequencing showed that all 3 drugs significantly increased the richness and diversity of gut microbiota in the model mice. Bioinformatic analysis revealed that the faeces of mice treated with ranitidine and finasteride, had significant increases in the number of microbes in the families g_Helicobacter, f_Desulfovibrionaceae, Mucispirillum_schaedleri_ASF457, and g_Blautia, whereas the relative abundances of microbes in the families Enterobacter_sp._IPC1-8 and g_Bacteroides were significantly reduced. The microbiota metabolic pathways, such as nucleotide and cofactor and vitamin metabolism were also significantly increased, whereas the activities of metabolic signalling pathways related to glycan biosynthesis and metabolism and cardiovascular diseases were significantly reduced. Therefore, our study indicates that in addition to their known pharmacological effects, ranitidine and finasteride also exhibit potential cardiovascular and renal protective effects. They inhibit the synthesis and metabolism of TMAO and delay the deposition of lipids and endotoxins through improving the composition of the gut microbiota.